Developing reading and writing skills through science fiction: I, robot by Issac Asimov - Maldonado Pérez, Marixa
Developing reading and writing skills are important for learners because they can communicate their feelings, thoughts, and emotional issues. For these reasons I chose them for working on my proposal which is about Science fiction and the novel ¨I, Robot¨ written by Isaac Asimov. Moreover, there is a brief reading about The Whole Language approach and some exercises based in the novel. The proposal begins with a short biography about the novel´s author Isaac Asimov and tells about his life, career, and death. Then there are introduction about science fiction and its issues. Reading and writing skills are developed. The Whole Language approach is mentioned in order that it is an available approach teachers should apply in their classes. It gives some cues on how to management classrooms and all related with it. This approach is according with educational curriculum. The exercises are the last activities which are focused on the novel I, Robot. The teachers should be conscious that the learning-teaching process is constantly changed. I hope this proposal helps some English teachers improve the skills on reading and writing, and changes the traditional methodology by applying the new technological devices.